Limit Properties of Transition Functions of Continuous-Time Markov Branching Processes. (16th October 2014) - Imomov, Azam A.
Abstract : Consider the Markov Branching Process with continuous time. Our focus is on the limit properties of transition functions of this process. Using differential analogue of the Basic Lemma we prove local limit theorems for all cases and observe invariant properties of considering process.